العوامل المؤثرة على الأداء الوظيفي للعاملين بديوان بلدية بنغازي - عبدالسلام محمد عبدالحفيظ (Scientific Journal of University of Benghazi, 2019)
This study aimed to identify factors affecting the employees' job performance in Benghazi municipality. Moreover, the study aimed to specify which of these factors are the most affecting. The population of this study consists of all employees in Benghazi municipality. The questionnaire was used as an essential tool for data collection, and the Statistical Package for Social Sciences (SPSS) was used to analyze the data. The results showed that there is a positive significant effect of factors affecting the employees' job performance on job performance, and the empowerment, clarity of responsibility and organizational culture had positive significant effect on job performance. The study concluded with some recommendations that are expected to improve employees' job performance in Benghazi municipality.